Insights Into Central Nervous System Glial Cell Formation and Function From Zebrafish - Neely, Sarah A.; Lyons, David A. (Frontiers in Cell and Developmental Biology, 2021)
The term glia describes a heterogenous collection of distinct cell types that make up a large proportion of our nervous system. Although once considered the glue of the nervous system, the study of glial cells has evolved significantly in recent years, with a large body of literature now highlighting their complex and diverse roles in development and throughout life. This progress is due, in part, to advances in animal models in which the molecular and cellular mechanisms of glial cell development and function as well as neuron-glial cell interactions can be directly studied in vivo in real time, in intact neural circuits. In this review we highlight the instrumental role that zebrafish have played as a vertebrate model system for the study of glial cells, and discuss how the experimental advantages of the zebrafish lend themselves to investigate glial cell interactions and diversity. We focus in particular on recent studies that have provided insight into the formation and function of the major glial cell types in the central nervous system in zebrafish.